The Use of Quizizz Online Software in the Evaluation of Arabic Learning - Al Munawaroh, Nisa Tazkiya (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2021)
Evaluation is an important stage in learning because it provides information about the implementation of the teaching and learning process, as well as in Arabic lessons. However, the evaluation media used are sometimes not as expected and do not provide convenience for the teacher. It also makes students respond negatively to learning. This study aims to explore and describe the use of Quizizz online software as a medium that facilitates the learning process. Participants in this study were an Arabic teacher and students of SMAN 11 Bandung. The approach used in this research is descriptive qualitative. The results of this study indicate that the use of Quizizz online software in evaluating Arabic learning contains principles that make it easier for teachers to process and get positive responses from students.